EFFORTS TO FULFILL THE HEALTH RIGHTS OF PRISONERS IN PLACES OF DETENTION - Riza Wira Pratiwi Lumbantoruan; Henry Aspan; Siti Nurhayati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
One of the rights of prisoners is to receive health insurance, but often detainees' health rights are not fulfilled. This is clearly very contradictory where in the Decree of the Minister of Justice of the Republic of Indonesia Number: M.02-PK.04.10 of 1990 concerning Patterns of Development for Prisoners/Detainees, the Minister of Justice of the Republic of Indonesia states in section C regarding health care. Apart from that, Law Number: 39 of 1999 concerning Human Rights Article 4 emphasizes the importance of fulfilling the health rights of prisoners and one of the rights that prisoners have is contained in Government Regulation Number: 58 of 1999 Article 9, namely regarding responsibility for prisoner care, prisoners have the right to receive prisoner care including physical and spiritual care, in terms of health services. However, its implementation is very difficult if it is carried out in accordance with existing regulations, because the expected conditions are different from the conditions in reality. In reality, we often find various kinds of obstacles faced by the management of places of detention, these obstacles include overcapacity in prisons, there is still a lack of special officers in the health sector in the management of places of detention which is still hampered by the problem of limited budget funds. .